Associations of dietary biotin intake on anxiety and depression: findings from a population-based prospective cohort study - Kong, Yan; Xia, Wei; Wang, Tong; Zhang, Dongfeng (Frontiers in Nutrition, 2026)
BackgroundSome cross-sectional have found the negative association between dietary biotin intake and anxiety and depression symptoms. However, there is still a lack of cohort study in this field. So we conduct this prospective cohort study to investigate the association between dietary biotin intake and anxiety and depression, evaluate their dose–response relationship and the mediating role of inflammation in this process.MethodsA total of 144,439 UK Biobank participants without baseline anxiety or depression were included. Dietary biotin intake was derived from the 24-h Oxford WebQ data, and anxiety and depression were defined in accordance with the ICD-10 criteria. Cox proportional hazards models and restricted cubic splines (RCS) were used to evaluate longitudinal associations. The Karlson-Holm-Breen method was used to examine the mediating effect of inflammation.ResultsA total of 144,439 participants were included in this study with a median follow-up of 14.06 years. Compared to Q1 group, dietary biotin intake was associated with a reduced risk of anxiety or depression (HR: 0.86 [0.82, 0.91] for Q2; HR: 0.84 [0.79, 0.88] for Q3; HR: 0.86 [0.81, 0.91] for Q4). Similar results were also found in anxiety, depression, and their comorbidity. RCS existed an approximately “L-shaped” dose–response relationship between biotin and both anxiety and depression. Except for depression and comorbidity, both single mediating indicators and composite mediating indicators played a partial mediating role in the course of this.ConclusionDietary biotin intake exhibited an approximately L-shaped nonlinear relationship with anxiety and depression risk, where risk decreased with increasing intake up to a moderate threshold, beyond which no further reduction was observed. This association may be partially mediated by inflammation.